2021
DOI: 10.3390/rs13132565
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Ecosystem Mapping Using Sentinel-1 and Sentinel-2 Satellite Images and Random Forest Algorithm in Google Earth Engine

Abstract: Mangroves are among the most productive ecosystems in existence, with many ecological benefits. Therefore, generating accurate thematic maps from mangrove ecosystems is crucial for protecting, conserving, and reforestation planning for these valuable natural resources. In this paper, Sentinel-1 and Sentinel-2 satellite images were used in synergy to produce a detailed mangrove ecosystem map of the Hara protected area, Qeshm, Iran, at 10 m spatial resolution within the Google Earth Engine (GEE) cloud computing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 77 publications
1
47
1
3
Order By: Relevance
“…The basic principle of this algorithm is to construct a collection of decision tree classifiers, each decision tree would give a classification choice by using the mechanism of multiple decision tree voting to improve the problem of easy overfitting of decision trees as well as the use of majority voting mechanism strategy to obtain the final output [52,53]. Compared with other machine learning methods, RF classification algorithm has better robustness and can run effectively on large datasets [54][55][56]. Some scholars have carried out relevant research on LULC classification by using the RF algorithm on the GEE platform and achieved excellent research results [57][58][59].…”
Section: Random Forestmentioning
confidence: 99%
“…The basic principle of this algorithm is to construct a collection of decision tree classifiers, each decision tree would give a classification choice by using the mechanism of multiple decision tree voting to improve the problem of easy overfitting of decision trees as well as the use of majority voting mechanism strategy to obtain the final output [52,53]. Compared with other machine learning methods, RF classification algorithm has better robustness and can run effectively on large datasets [54][55][56]. Some scholars have carried out relevant research on LULC classification by using the RF algorithm on the GEE platform and achieved excellent research results [57][58][59].…”
Section: Random Forestmentioning
confidence: 99%
“…Studies have shown that the integration of Sentinel-1 and Sentinel-2 can improve the accuracy of mapping land cover [39,40]. Two sensitive vegetation indices, the normalized difference vegetation index (NDVI) and the enhanced vegetation index (EVI), were selected based on Sentinel-2 data.…”
Section: Classification System and Classification Feature Setsmentioning
confidence: 99%
“…Several works proposed this approach as a way of assessing quantitatively the forest yield, forest biomass, and carbon dynamics from high-resolution remote sensing or UAV-based imagery [15][16][17][18][19][20][21][22]. The inventory from a certain ecosystem can also be estimated by mapping it through satellite images, as was made in [23] for a mangrove ecosystem. The authors used a pixelbased random forest classifier that resulted in a mangrove map with an overall accuracy of 93%.…”
Section: Vision-based Perceptionmentioning
confidence: 99%